Hubungan Antara Kejadian Malaria dengan Status Gizi Balita - Muhammad Tarmidzi, Soesanto Tjokrosonto, Toto Sudargo (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Malaria is one amongst the major health problems in Kulonprogo District of Yogyakarta Province. The district itself is high case incidence (HCI) area, particularly in Kokap and Samigaluh Subdistricts. Even though malaria might affect nutritional status, their relationship is still controversial, particularly among children under five years old.Methods: This study was designed as a retrospective nested case control study. The study was conducted in Kokap and Samigaluh Subdistricts over 3 months period starting on August 2004. Cases were children under five years old who suffered under nutrition and severe malnutrition. Controls were healthy children who did not suffer malnutrition. Data were processed by computer program. Bivariate analysis was conducted to assessthe association between nutritional status and malaria.Results: The study showed that there were no association between malaria and nutritional status among children under five years old in Kokap and Samigaluh Subdistricts of Kulonprogo Region, Daerah Istimewa Yogyakarta Province (p=0.308). The odds ratio of having malaria among cases was 1.54 (95%CI=0.62 - 3.87).Conclusión: There were no association between malaria and nutritional status among children under five in Kokap and Samigaluh Subdistricts of Kulonprogo Region, Daerah Istimewa Yogyakarta Province.Keywords: malaria, incidence, nutritional status, under five year children